2021
DOI: 10.1590/s1980-220x2019040003693
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the operational conditions of crash carts in clinical and surgical hospitalization units

Abstract: Objective: To evaluate the operational conditions of crash carts in all clinical and surgical hospitalization units of public hospitals in a region in Southern Brazil. Method: Quantitative, cross-sectional study to evaluate crash carts in adult clinical and surgical hospitalization units. The data were collected through a checklist containing 16 continuous variables. Results: Nineteen crash carts in nineteen units were evaluated. Analysis shows that the most frequent problems were excess of equipment and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Hence, the preference to switch to a weekly control of the full checklist, rather than a daily check. Finally, the new nursing coordinator, although she did not fill in the questionnaire for the survey of opinions on the new garrison since she had recently taken office, still considered it appropriate to move the portable oxygen cylinder in the adjacent business premises, for the alleged explosive risk due to the presence of cables and wires of the monitors on the trolley, although this recommendation had not emerged from the results of the systematic review conducted for the development of the original thesis product [8].…”
Section: Questionmentioning
confidence: 99%
“…Hence, the preference to switch to a weekly control of the full checklist, rather than a daily check. Finally, the new nursing coordinator, although she did not fill in the questionnaire for the survey of opinions on the new garrison since she had recently taken office, still considered it appropriate to move the portable oxygen cylinder in the adjacent business premises, for the alleged explosive risk due to the presence of cables and wires of the monitors on the trolley, although this recommendation had not emerged from the results of the systematic review conducted for the development of the original thesis product [8].…”
Section: Questionmentioning
confidence: 99%
“…8 Different studies have shown that initiation of CPR is delayed due to a lack of medicines and functioning equipment. [9][10][11] The incidence of cardiac arrest is high in cardiac hospitals. Therefore, crash cart and staff working in a cardiac center should always be ready to tackle cardiopulmonary resuscitation (whether it is in a critical care setting or a general ward).…”
Section: Introductionmentioning
confidence: 99%